Chinese Black Truffle-Associated Bacterial Communities of Tuber indicum From Different Geographical Regions With Nitrogen Fixing Bioactivity - Chen, Juan; Li, Jia-Mei; Tang, Yan-Jing; Xing, Yong-Mei; Qiao, Peng; Li, Yang; Liu, Pei-Gui; Guo, Shun-Xing (Frontiers in Microbiology, 2019)
It is well known that the microbes associated with truffle fruiting bodies play a very important role during the truffle lifecycle. Tuber indicum, commonly called Chinese black truffle, is a species endemic to Eastern Asia and in the genus of Tuber. Here, we reported the bacterial communities of T. indicum from different geographical regions and described the bacterial diversity from three compartments (soil, ectomycorrhizae and ascocarps) of T. indicum using high-throughput sequencing combined tissue culture. The results revealed that Bradyrhizobium was the dominant genus in fruiting bodies of T. indicum from nine geographical sites in China, and the microbes in T. indicum ascocarps were influenced by geological locations and soil characteristics. More specific bacterial taxa were enriched in the fruiting bodies than in the ectomycorrhizae and soil. In addition, 60 cultural bacteria were isolated from T. indicum fruiting bodies (4 families, 24 genera), and Pseudomonas, Alcaligenes faecalis, Microbacterium and Arthrobacter were dominant. One of 13 strains that have potential nitrogen-fixation activities was further verified by an acetylene reduction assay. Together, this research provides new and important data for better understanding of the interaction between truffle and associated microbe and the biology of truffle itself.